Magi : the labyrinth of magic. 36 - Otaka, Shinobu (Magi, 2019)
Inside the Sacred Palace, Alibaba<U+2019>s experience after death drives him to make Sinbad see reason, but the Great Flow is suddenly disturbed! Confusion and chaos descend on the earth<U+2019>s surface, and friends become foes as Aladdin, Alibaba, Judar and Sinbad fight to reclaim their home...